Carbohydrate esterases involved in deacetylation of food components by the human gut microbiota. Issue 3 (18th April 2023) - La Rosa, Sabina Leanti; Lindstad, Lars J.; Westereng, Bjørge
Abstract: Non-carbohydrate modifications such as acetylations are widespread in food stuffs as well as they play important roles in diverse biological processes. These modifications meet the gut environment and are removed from their carbohydrate substrates by the resident microbiota. Among the most abundant modifications are O -acetylations, contributing to polysaccharides physico-chemical properties such as viscosity and gelling ability, as well as reducing accessibility for glycosyl hydrolases, and thus hindering polysaccharide degradation. Of particular note, O -acetylations increase the overall complexity of a polymer, thus requiring a more advanced degrading machinery for microbes to utilize it. This minireview describes acetylesterases from the gut microbiota that deacetylate various food polysaccharides, either as natural components of food, ingredients, stabilizers of microbial origin, or as part of microbes for food and beverage preparations. These enzymes include members belonging to at least 8 families in the CAZy database, as well as a large number of biochemically characterized esterases that have not been classified yet. Despite different structural folds, most of these acetylesterases have a common acid–base mechanism and belong to the SGNH hydrolase superfamily. We highlight examples of acetylesterases that are highly specific to one substrate and to the position of the acetyl group on the glycosyl residue of the carbohydrate, while other members that have more broad substrate specificity. Current research aimed at unveiling the functions and regioselectivity of acetylesterases will help providing fundamental mechanistic understanding on how dietary components are utilized in the human gut and will aid developing applications of these enzymes to manufacture novel industrial products.